Nivel de conocimiento del riesgo de embarazo adolescente en el Colegio de Bachillerato Macará - Varón Padilla, John Edwin (2023)
Adolescent pregnancy and early motherhood are social problems that affect the development of the lives of thousands of adolescents in Latin America and Ecuador. This research focused on the objectives of determining the sociodemographic characteristics of the student population, identifying the level of knowledge of the risk of teenage pregnancy, and implementing actions on teenage pregnancy prevention in the daytime section of the Colegio de Bachillerato Macará. For this purpose, a quantitative, descriptive and cross-sectional study was conducted with a non-probabilistic sample of 100 adolescent women from 8th to 3rd year of high school of the institution, which allowed evaluating the level of knowledge of the risk of teenage pregnancy, obtaining as a result: the average age was 13 to 15 years old, residents of the Macará canton, 68% live with both parents, 48% have a medium level of knowledge, followed by 41% with a low level of knowledge about the risk of teenage pregnancy. Forty-seven percent obtain information about sex education from their friends and 26% self-educate with information sources from the Internet. In conclusion, the level of knowledge about the risk of teenage pregnancy of the students of the Colegio de Bachillerato Macará is medium to improve, the prevention guide was socialized to the authorities for its application.